Wide variation in absolute cardiovascular risk assessment in Aboriginal and Torres Strait Islander people with Type 2 diabetes - Bhakti Ramesh Vasant; Veronica eMatthews; Christopher Paul Burgess; Chistine M Connors; Ross Stewart Bailie (Frontiers Media S.A., 2016)
Background: Absolute cardiovascular risk assessment (CVRA) is based on the combined effects of multiple risk factors and can identify asymptomatic individuals at high risk of cardiovascular disease. Aboriginal and Torres Strait Islander people are disproportionately affected by cardiovascular disease and diabetes. Our study aimed to investigate variations in the use of absolute CVRA in patients with diabetes at Indigenous community healthcare centres, and to identify patient and health centre characteristics that may contribute to this variation. Methods: Audits of clinical records of 1,728 patients with a known diagnosis of diabetes across 121 health centres over the period 2012-2014 were conducted as part of a large-scale continuous quality improvement program. Multilevel regression modelling was used to quantify variation in recording of CVRA attributable to health centre and patient characteristics. Results: The proportion of eligible patients with documented CVRA was 33% (n=574/1,728). The majority (95%) of assessments were conducted in the Northern Territory (NT). Multilevel regression analysis showed health centre characteristics accounted for 70% of the variation in assessments in the NT. Government-operated health centres had 18.8 times the odds (95% CI 7.7-46.2) of recording CVRA delivery compared with other health centres. Conclusion: Health centres in the NT delivered the majority of absolute CVRA to Indigenous patients with diabetes in our study. Health systems factors that may have facilitated provision of CVRA in the NT include decision support tools and a reporting process for CVRA delivery. Implementation of similar systems in other jurisdictions may help improve CVRA delivery. Early identification and treatment of high risk individuals through wider use of CVRA may help reduce the burden of cardiovascular disease in Indigenous Australians with diabetes.